Kit iTCLab Application as a Learning Tool for the Internet of Things - Maulana, Asrul; Rahmat, Basuki; Matalangi, Matalangi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The rapid advancement of the Internet of Things (IoT) has created opportunities for transformative innovations in various technology-based learning sectors, particularly through Smart Kits. This study aims to develop and implement the Internet-Based Temperature Control Lab (iTCLab) Kit as an interactive learning tool for IoT. The iTCLab application is designed to enable users to monitor and control temperature in real-time via an internet-based platform. The system utilizes temperature sensors, heating actuators, an ESP32 microcontroller, and an internet connection. Testing was conducted through the Microcontroller course in the Informatics Study Program. The results indicate that the iTCLab Kit significantly enhances students' understanding and mastery of practical IoT programming. Thus, the iTCLab Kit serves as an innovative solution to support more effective and efficient IoT learning.